2016
DOI: 10.1136/jim-2016-000190
|View full text |Cite
|
Sign up to set email alerts
|

Tea Flavonoids for Bone Health: From Animals to Humans

Abstract: Osteoporosis is a skeletal disease characterized by a deterioration of bone mass and bone quality that predisposes an individual to a higher risk of fragility fractures. Emerging evidence has shown that the risk for low bone mass and osteoporosis-related fractures can be reduced by nutritional approaches aiming to improve bone microstructure, bone mineral density, and strength. Tea and its flavonoids, especially those of black tea and green tea, have been suggested to protect against bone loss and to reduce ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 69 publications
0
29
0
1
Order By: Relevance
“…Furthermore, in a double-blind controlled study, type 2 diabetes patients had improvements in obesity and glucose levels after 582.8 mg or 96.3 mg consumption of catechins for 12 weeks [235]. Bone health improvements and Alzheimer's disease prevention by catechins in pre-clinical and clinical studies were summarized somewhere else [236,237].…”
Section: Catechinsmentioning
confidence: 99%
“…Furthermore, in a double-blind controlled study, type 2 diabetes patients had improvements in obesity and glucose levels after 582.8 mg or 96.3 mg consumption of catechins for 12 weeks [235]. Bone health improvements and Alzheimer's disease prevention by catechins in pre-clinical and clinical studies were summarized somewhere else [236,237].…”
Section: Catechinsmentioning
confidence: 99%
“…[44,45] EGCG has been widely studied. Its beneficial effects on bone formation are mainly through increasing alkaline phosphatase activity at both the protein and gene expression levels in osteoblastic-like cells, including SaOS-2 cells [46] and MC3T3-E1 cells, and increased formation of mineralized bone.…”
Section: Discussionmentioning
confidence: 99%
“…Isoflavones are "natural" or "phytoestrogens" (e.g., bioactive compounds that bind to the estrogen receptor) found in various plants and foods, most notably soybeans. Tea flavonoids have been suggested to protect against bone loss, but epidemiologic studies have shown mixed results of habitual tea consumption on BMD and fracture risk, and the results from clinical trials are limited (94). There has been increasing interest in whether isoflavones can promote bone health and ameliorate bone loss (95), but studies are conflicting regarding a positive BMD effect (96).…”
Section: Macronutrients and Isoflavonesmentioning
confidence: 99%